Beliefs and behavioural responses to constipation among elderly Malays in north-eastern Peninsular Malaysia - Abdul Wahab, Patimah; Yeong, Yeh Lee; Ali, Siti Hawa; Abdul Kadir, Azidah; Mohd Yusoff, Dariah (The Continence Foundation of Australia and The New Zealand Continence Association, 2017)
Beliefs and behavioural responses to constipation may be different in an elderly population of Malay ethnicity. An exploratory study, based on a grounded theory approach, used a semistructured interview to collect data from elderly residents from the north-eastern region of Peninsular Malaysia. A total of 46 elderly people (29 women and 17 men) of Malay ethnicity participated. The study demonstrated that this population had unique beliefs and behavioural responses towards constipation. Specifically, they viewed symptoms associated with constipation as taboo, mild or of low impact, were related to diet and were a part of the normal ageing process. Participants described ways they selfmanaged constipation, including the use of home remedies. However, whether successful or not in their self-management, they adapted to their symptoms over time unless severe, or they developed haemorrhoids. This study identified and highlighted the importance of including screening for constipation when assessing the health of an older person and educating older people about constipation.